2018
DOI: 10.1021/acs.jafc.8b02949
|View full text |Cite|
|
Sign up to set email alerts
|

Sulforaphane Rescues Ethanol-Suppressed Angiogenesis through Oxidative and Endoplasmic Reticulum Stress in Chick Embryos

Abstract: Our previous study showed that ethanol exposure inhibited embryonic angiogenesis mainly due to the excessive stimulation of reactive oxygen species (ROS) production. In this study, we investigated whether sulforaphane (SFN), a known dietary bioactive compound, could ameliorate ethanol-suppressed angiogenesis using chick embryo angiogenesis models. Using chick yolk sac membrane (YSM) and chorioallantoic membrane (CAM) models, we demonstrated that administration of low concentrations of SFN (2.5-10 μM) alone inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
(113 reference statements)
0
15
0
Order By: Relevance
“…Sulforaphane (SFN) is a natural isothiocyanate extracted from cruciferous plants. SFN has been used in the treatment of diabetic cardiomyopathy (5), angiogenesis (6) and cancer (7). The main pathway regulated by SFN is the Keap-1/nuclear factor erythroid 2-related factor 2 (Nrf2) pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…Sulforaphane (SFN) is a natural isothiocyanate extracted from cruciferous plants. SFN has been used in the treatment of diabetic cardiomyopathy (5), angiogenesis (6) and cancer (7). The main pathway regulated by SFN is the Keap-1/nuclear factor erythroid 2-related factor 2 (Nrf2) pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…It is effective against oxidative-induced cardiomyocyte damage ( 51 ). Moreover, SFN has been shown to be effective against ERS in different models of cell injury, including chick yolk sac membrane and chorioallantoic membrane models ( 52 ). It inhibits ERS by suppressing the apoptosis of cells in type 1 diabetes mellitus ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-apoptotic effect of SFN was also found to be present in human hepatocytes ( 54 ). Wang et al ( 52 ) reported that SFN ameliorates ethanol-suppressed embryonic angiogenesis by alleviating excessive ROS production and ERS. Moreover, Li et al ( 26 ) documented that SFN suppresses expression levels of ERS-associated apoptosis proteins by activating SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo mortality in the experimental groups of our study was the highest in the 200μM PhIP group in terms of the median lethal dose (LD50) and neural tube malformation rates. Therefore, 200μM PhIP was selected for the treatment group, and a 5μM Nano-SFN intervention was chosen based on existing literature (G. Wang et al, 2018). The results showed that Nano-SFN reduced PhIP-induced embryonic death and NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…SFN can protect cells from DNA damage (Russo et al, 2018) and is a potent antioxidant (Negrette-Guzman, 2019;Negrette-Guzman et al, 2013), which inhibits oxidative damage caused by various factors in neurons, glial cells, microglia and astrocytes (Danilov et al, 2009;Greco et al, 2010;Hong et al, 2005;Innamorato et al, 2008;Kraft et al, 2004;Soriano et al, 2008). In our previous study, we found that 5-10μM SFN significantly rescued ethanol-suppressed angiogenesis in chick embryos (G. Wang et al, 2018). Nano-sized medicine, in comparison with conventional medicine, leads to increased active concentrations and bioavailability (Balakumar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%